Comprehensive solid fuel modification method based on flue gas micro-nano bubbles

By introducing flue gas micro-nano bubbles and undesulfurized flue gas into solid fuel modification, the comprehensive modification of solid fuel is achieved, solving the problems of single function and high cost of modification methods in the prior art, and improving the fuel calorific value and environmental friendliness.

CN119177133AActive Publication Date: 2024-12-24HUAZHONG UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411574758.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-24
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing solid fuel modification methods have a single function, and cannot achieve comprehensive modification of solid fuels, and are costly, which is not conducive to industrial applications.

Method used

Using a comprehensive modification method of solid fuel based on flue gas micro-nano bubbles, the undesulfurized flue gas is passed into the mixed slurry of solid fuel in the form of micro-nano bubbles, and the combined action of multiple radicals and complex flue gas components is carried out. Demineralization treatment achieves improvements in physical and chemical properties of solid fuels.

Benefits of technology

Comprehensive modification of solid fuels is achieved, the calorific value is improved, the tendency of contamination and slag during combustion is weakened, and particulate matter emissions are reduced. It is simple to operate, mild conditions, low cost and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177133A_ABST
    Figure CN119177133A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solid fuel modification, and particularly discloses a solid fuel comprehensive modification method based on flue gas micro-nano bubbles, and the method comprises the following steps: dissolving a solid fuel to be modified in a liquid solvent to obtain mixed slurry; then introducing the non-desulfurized flue gas into the mixed slurry in the form of micro-nano bubbles; and finally, carrying out solid-liquid separation and drying treatment on the modified mixed slurry to obtain the modified solid fuel. The non-desulfurized flue gas is introduced into the mixed slurry in the form of micro-nano bubbles, and the combined action of the sulfur-containing flue gas and the micro-nano bubbles is utilized, so that on one hand, mineral substances in the solid fuel can be removed, the heat value of the solid fuel is effectively increased, the contamination and slagging tendency in the combustion process is weakened, and the discharge amount of particulate matters is reduced; on the other hand, physical characteristics and chemical characteristics of the solid fuel, such as a carbon structure, a pore structure, hydrophilicity and hydrophobicity, free radicals and the like, can be improved, subsequent high-value utilization of the solid fuel is facilitated, and comprehensive modification of the solid fuel is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of solid fuel modification, and more specifically, relates to a comprehensive modification method of solid fuel based on flue gas micro-nano bubbles. Background Art

[0002] my country has abundant reserves of coal resources, but limited reserves of high-quality coal resources, and the distribution clearly shows a state of "more in the west and less in the east, poor in the south and rich in the north". Coal reserves are mainly concentrated in Shanxi, Shaanxi, Inner Mongolia and Xinjiang, accounting for more than 70% of the country's coal reserves. In addition, various types of coal have problems such as regional imbalance in production and use of coal, and mismatch in production and use of coal in terms of reserves, regional distribution and differences in coal quality demand, which greatly limits the comprehensive utilization efficiency of my country's coal resources. At the same time, other solid fuels such as biomass and solid waste also have the problem of poor direct utilization effect. Therefore, the modification of solid fuels is of great significance to ensure my country's energy security and green development.

[0003] After solid fuels are modified by physical, chemical or biological methods, the relevant properties of solid fuels can be effectively improved to meet specific industrial application needs, such as enhancing combustion / gasification / liquefaction efficiency, reducing pollutant emissions, improving coal quality, preparing special materials, etc. However, the solid fuel modification methods in the prior art are relatively single in function and can only meet specific industrial needs, but cannot achieve comprehensive modification and quality improvement of solid fuels. In addition, they have the problems of high cost and disadvantageous for industrial application. Summary of the invention

[0004] In view of the defects of the prior art, the present application provides a comprehensive modification method of solid fuel based on flue gas micro-nano bubbles, aiming to solve the problem that the existing modification methods have single functions and cannot achieve comprehensive modification.

[0005] According to one aspect of the present application, a comprehensive modification method of solid fuel based on flue gas micro-nano bubbles is provided, specifically:

[0006] S1 dissolving the solid fuel to be modified in a liquid solvent to obtain a mixed slurry;

[0007] S2 introduces the undesulfurized flue gas into the mixed slurry in the form of micro-nano bubbles, so that under the joint action of the multi-free radicals generated by the micro-nano bubbles and the complex flue gas components, the solid fuel is demineralized and the physical and chemical properties of the solid fuel are improved, thereby achieving comprehensive modification of the solid fuel;

[0008] S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified solid fuel.

[0009] Through the above technical scheme conceived by the present application, compared with the prior art, since the present application introduces micro-nano bubbles into the solid fuel modification, it can achieve physical and chemical modifications while carrying out demineralization treatment in combination with undesulfurized flue gas, thereby achieving comprehensive modification of solid fuel.

[0010] As further preferred, in step S1, the liquid solvent is pure water, boiler drum water, domestic water or water after deep treatment in a desulfurization wastewater treatment system.

[0011] As further preferred, in step S1, the particle size of the solid fuel to be modified is less than 200 μm.

[0012] As further preferred, in step S1, the solid-to-liquid ratio of the mixed slurry is 1:20 to 1:50.

[0013] As further preferred, in step S2, the size of the micro-nano bubbles is 100 nm to 10 μm.

[0014] As further preferred, in step S2, the treatment time is 30 min to 2 h, and the treatment temperature is 20° C. to 80° C.

[0015] As further preferred, in step S2, the slurry is stirred while the flue gas is introduced, and the stirring rate is 200 r / min to 1500 r / min.

[0016] According to another aspect of the present application, a modified solid fuel prepared by the above method is provided.

[0017] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art:

[0018] 1. The present application, by passing undesulfurized flue gas in the form of micro-nano bubbles into a mixed slurry containing solid fuel, utilizes the combined action of sulfur-containing flue gas and micro-nano bubbles, on the one hand, can remove minerals such as alkali metals and alkaline earth metals in the solid fuel, thereby effectively improving the calorific value of the solid fuel, and reducing the tendency of contamination and slagging during the combustion process, and reducing the emission of particulate matter; on the other hand, it can achieve improvements in the physical and chemical characteristics of the solid fuel, such as carbon structure, pore structure, hydrophilicity, free radicals, etc., which is conducive to the subsequent high-value utilization of the solid fuel, thereby achieving comprehensive modification of the solid fuel, and has the advantages of simple operation, mild conditions, and low cost, and has a relatively broad application prospect;

[0019] 2. At the same time, the present application can increase the content of ·OH and ·H radicals in the aqueous solution by optimizing the solid-liquid ratio and the size of the micro-nano bubbles, thereby obtaining the best solid-liquid ratio under the most economical conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a flow chart of a comprehensive modification method of solid fuel based on flue gas micro-nano bubbles provided in an embodiment of the present application;

[0021] Figure 2 The removal rate of minerals in the modified coal obtained in Example 1 and Comparative Examples 1 to 3 of the present application;

[0022] Figure 3 The total content of acid infusible minerals in the modified coal obtained in Example 1 and Comparative Examples 1 to 3 of the present application;

[0023] Figure 4 are the microcrystalline structure parameters of the modified coal obtained in Example 1 and Comparative Examples 1 to 3 of the present application, wherein (a) is d002, (b) is La, (c) is Lc, and (d) is fa;

[0024] Figure 5 The carbon structure parameter changes of the modified coal obtained in Example 1 and Comparative Examples 1 to 3 of the present application;

[0025] Figure 6 The S / N morphological distribution characteristics in the modified coal are obtained in Example 1 and Comparative Examples 1 to 3 of the present application, wherein (a) is the morphological distribution characteristics of the S element in the modified coal, and (b) is the morphological distribution characteristics of the N element in the modified coal. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0027] like Figure 1 As shown, according to one aspect of the present application, a comprehensive modification method of solid fuel based on flue gas micro-nano bubbles is provided, specifically:

[0028] S1: crushing, grinding and screening the solid fuel to be modified, and then dissolving it in a liquid solvent to obtain a mixed slurry;

[0029] S2 introduces the undesulfurized flue gas into the mixed slurry in the form of micro-nano bubbles, so that the solid fuel is demineralized and the physical and chemical properties of the solid fuel are improved under the combined action of the multi-free radicals generated by the micro-nano bubbles and the complex flue gas components, thereby achieving comprehensive modification of the solid fuel and effectively reducing SO2, CO2 and NO in the flue gas. x content, achieving the effect of flue gas coordinated treatment;

[0030] S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified solid fuel, wherein a high-temperature flue gas can be introduced to perform drying treatment through heat exchange, thereby further reducing production costs.

[0031] This application introduces micro-nano bubbles into the modification of solid fuels, and cooperates with undesulfurized flue gas to achieve physical and chemical modification while performing demineralization treatment, thereby achieving comprehensive modification of solid fuels, effectively solving the problem of single function and poor effect of modification methods in the prior art. At the same time, this application uses the flue gas of the power plant itself to modify and pretreat the solid fuel, which is not only simple in process and low in cost, but also can synergistically remove SO2 from the flue gas, effectively improve the overall removal efficiency of SO2 in the flue gas, and reduce the desulfurization tower and the use of desulfurizers, thereby further reducing the operating costs of the power plant.

[0032] In terms of demineralization, the present application has a high demineralization efficiency, can effectively improve the calorific value of solid fuels, and at the same time reduce the tendency of contamination and slagging during combustion, and reduce the emission of particulate matter. During the modification process, the solubility of acidic gases in flue gas in water can be enhanced by generating flue gas micro-nano bubbles, significantly reducing the pH of the mixed slurry, and effectively removing alkali metals and alkaline earth metals (AAEMs) in the form of ion exchange and acid soluble in solid fuels. At the same time, due to the presence of flue gas micro-nano bubbles, more OH radicals, O radicals, etc. will be produced. Compared with the free H radicals that can only be provided by the acid solution in the pickling modification, the free radicals have stronger electronic energy, which can destroy the Al-O bond in the AAEMs aluminosilicate / silicate lattice structure to obtain Si-O bonds, thereby promoting the acid-insoluble AAEMs to transform into other forms, and improving the removal efficiency of AAEMs as a whole. The present application can also simultaneously remove some trace elements in solid fuels, reduce the enrichment of toxic elements in solid fuels, and reduce the toxicity of particulate matter. In addition, the present application utilizes the reaction of flue gas acid gases (SO2, CO2, HCl, etc.) with water in the form of micro-nano bubbles, and the formed mixed acidic solutions of H2SO3, H2SO4, H2CO3, HCl, etc., to achieve enhanced and efficient removal of inorganic impurities in solid fuels.

[0033] In terms of physical modification, this application can achieve the following effects:

[0034] (1) Changing the carbon structure: Flue gas micro-nano bubbles will produce strong oxidizing free radicals such as ·OH and ·O in water. These free radicals can effectively destroy the complex organic structure in the solid fuel, destroy the aromatic ring structure in the solid fuel, and reduce the aromatization degree of the solid fuel, thereby improving the thermal utilization (pyrolysis, combustion, gasification, etc.) efficiency of the solid fuel. They can also promote the breakage of the branch and bridge chains in the solid fuel and reduce the molecular weight of the solid fuel, thereby improving the liquefaction efficiency of the solid fuel.

[0035] (2) Pore change: Since strong oxidizing free radicals such as ·OH and ·O can destroy the complex organic structure in the solid fuel, reduce the degree of aromatization and molecular weight, and more effectively open the pores inside the solid fuel to form a pore-rich structure, it can also simultaneously increase the specific surface area of ​​the solid fuel particles, further improving the thermal utilization efficiency of the solid fuel. At the same time, if the solid fuel is subsequently processed into activated carbon, the larger specific surface area and pore structure can effectively increase the adsorption capacity of the activated carbon.

[0036] (3) Hydrophilicity and hydrophobicity: During the continuous generation of flue gas micro-nano bubbles, more ·OH free radicals will be generated. During the reaction with solid fuel, the ·OH free radicals will increase the -OH functional groups in the solid fuel particles, thereby increasing the hydrophilicity of the solid fuel and helping to improve the dispersibility and stability of the solid fuel in water. For the preparation of water-coal slurry, the increase in hydrophilicity can reduce the aggregation between coal particles and improve the fluidity of water-coal slurry, thereby improving its overall performance. At the same time, the increase in the hydrophilicity of coal will also increase the viscosity of coal, so that it can become a high-viscosity coal to replace coking coal.

[0037] If it is necessary to change the hydrophilicity or hydrophobicity of coal, the flue gas micro-nano bubble generating device can be subsequently turned off, and only flue gas components can be continuously introduced into the water. The H free radicals and water molecules generated by the O2, SO2 and other gases in the flue gas components dissolving in water can react with the functional groups on the surface of the solid fuel, thereby reducing the content of the -OH functional group and reducing the hydrophilicity of the solid fuel. The -OH functional groups will be partially replaced to generate linear or branched alkyl hydrocarbons, alkyl phenols and other hydrophobic groups, and even the solid fuel will become a hydrophobic solid fuel.

[0038] In terms of chemical modification, sulfur-containing molecular structures such as thiophene / sulfone / sulfoxide and nitrogen-containing molecular structures such as pyridine / pyrrole in coal have high thermal stability. Desulfurization and denitrification require relatively high temperatures. Flue gas micro-nano bubbles produce strong oxidizing free radicals such as ·OH and ·O in water, which can effectively destroy these stable sulfur- and nitrogen-containing organic molecular structures to form sulfur free radicals such as ·SH and RS· and nitrogen free radicals such as ·NH2, ·NR2, and ·NO2. These free radicals have low thermal stability and are easier to remove, which can help the subsequent high-value utilization of solid fuels.

[0039] In other aspects, the method provided by the present application can be carried out at room temperature and pressure, with a simple operation method and mild operating conditions. At the same time, the gas source used in the present application is power plant flue gas, which is low in cost and easy to obtain. If the flue gas also contains a high concentration of Cl or NO x content, the solid fuel modification effect will be further improved.

[0040] In addition, after the flue gas is modified by micro-nano bubbles, the SO2 content in the flue gas will be effectively reduced. If there is a high concentration of Cl or NO in the flue gas, x The content can be reduced during the process of flue gas micro-nano bubble modification. The flue gas then enters the desulfurization tower, which can effectively reduce the operating load of the desulfurization tower, reduce the amount of desulfurizer used, save costs, and reduce the content of harmful gases discharged into the atmosphere. If multiple solid fuel modification devices are connected in series, they can even replace the role of the desulfurization tower. The coal washing wastewater obtained after solid-liquid separation of the modified mixed slurry can be connected to the desulfurization wastewater treatment unit without the need for an additional coal washing wastewater treatment system.

[0041] Furthermore, in step S1, pure water is the best liquid solvent, and boiler drum water, domestic water or water deeply treated by a desulfurization wastewater treatment system (water treated by reverse osmosis, mechanical steam recompression or multiple-effect evaporation of the clean water in the upper part of the clarification tank) can also be used, thereby effectively reducing the modification cost.

[0042] Furthermore, in step S1, the particle size of the solid fuel to be modified should not be too large, and can be less than 200 μm. The optimal particle size ranges of different types of solid fuels are different. The particle size of coal used in power plants is generally less than 100 μm, which meets the requirements.

[0043] Furthermore, in step S1, the solid-liquid ratio of the mixed slurry is 1:20 to 1:50. By optimizing the solid-liquid ratio of the mixed slurry, the modification effect and the amount of water can be balanced to achieve the optimal modification effect under the optimal solid-liquid ratio. If the solid-liquid ratio is too high, the AAEMs ion concentration in the aqueous solution will reach saturation too quickly. If the solid-liquid ratio is too low, although the modification effect can be achieved quickly, it will cause a great waste of water after exceeding the threshold range of the optimal solid-liquid ratio.

[0044] Furthermore, in step S2, the undesulfurized flue gas can be drawn from the back of the dust collector and the front of the desulfurization tower of the power plant. Its composition is relatively complex, mainly CO2, SO2 and O2, and contains a small amount of escaped NO x The undesulfurized flue gas can be introduced into the micro-nano bubble generating device, and then the micro-nano bubble generating device can pass the undesulfurized flue gas into the mixed slurry in the form of micro-nano bubbles.

[0045] Furthermore, in step S2, the size of the micro-nano bubbles is 100 nm to 10 μm. By optimizing the size of the micro-nano bubbles, the content of ·OH and ·H free radicals in the aqueous solution can be increased, thereby obtaining the best solid-liquid ratio under the most economical conditions.

[0046] Furthermore, in step S2, the treatment time is 30 minutes to 2 hours, and the treatment temperature is 20°C to 80°C.

[0047] Furthermore, in step S2, the slurry is stirred while the flue gas is introduced to promote solid-liquid contact, and the stirring rate is 200 r / min to 1500 r / min.

[0048] According to another aspect of the present application, a modified solid fuel prepared by the above method is provided.

[0049] The technical solution provided in this application is further described below based on specific embodiments.

[0050] Example 1

[0051] S1: dissolving the coal to be modified in deionized water to obtain a mixed slurry, wherein the solid-liquid ratio of the mixed slurry is 1:20;

[0052] S2 uses 3000ppm SO2+5%O2+15%CO2 mixed with balance gas N2 to simulate undesulfurized flue gas, and introduces it into the mixed slurry in the form of micro-nano bubbles. The size of the micro-nano bubbles is 1μm, the treatment time is 30min, the treatment temperature is 25℃, and the stirring rate is 800r / min, so as to achieve comprehensive modification of solid fuel;

[0053] S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified coal.

[0054] Example 2

[0055] S1: dissolving the coal to be modified in deionized water to obtain a mixed slurry, wherein the solid-liquid ratio of the mixed slurry is 1:50;

[0056] S2 uses 3000ppm SO2+5%O2+15%CO2 mixed with balance gas N2 to simulate undesulfurized flue gas, and introduces it into the mixed slurry in the form of micro-nano bubbles. The size of the micro-nano bubbles is 500nm, the treatment time is 1h, the treatment temperature is 30℃, and the stirring rate is 200r / min, so as to achieve comprehensive modification of solid fuel;

[0057] S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified coal.

[0058] Example 3

[0059] S1: dissolving the coal to be modified in deionized water to obtain a mixed slurry, wherein the solid-liquid ratio of the mixed slurry is 1:30;

[0060] S2 uses 3000ppm SO2+5%O2+15%CO2 mixed with balance gas N2 to simulate undesulfurized flue gas, and introduces it into the mixed slurry in the form of micro-nano bubbles. The size of the micro-nano bubbles is 100nm, the treatment time is 50min, the treatment temperature is 20℃, and the stirring rate is 1500r / min, so as to achieve comprehensive modification of solid fuel;

[0061] S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified coal.

[0062] Example 4

[0063] S1: dissolving the coal to be modified in deionized water to obtain a mixed slurry, wherein the solid-liquid ratio of the mixed slurry is 1:35;

[0064] S2 uses 3000ppm SO2+5%O2+15%CO2 mixed with balance gas N2 to simulate undesulfurized flue gas, and introduces it into the mixed slurry in the form of micro-nano bubbles. The size of the micro-nano bubbles is 10μm, the treatment time is 2h, the treatment temperature is 50℃, and the stirring rate is 300r / min, so as to achieve comprehensive modification of solid fuel;

[0065] S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified coal.

[0066] Example 5

[0067] S1: dissolving the coal to be modified in deionized water to obtain a mixed slurry, wherein the solid-liquid ratio of the mixed slurry is 1:25;

[0068] S2 uses 3000ppm SO2+5%O2+15%CO2 mixed with balance gas N2 to simulate undesulfurized flue gas, and introduces it into the mixed slurry in the form of micro-nano bubbles. The size of the micro-nano bubbles is 5μm, the treatment time is 1.5h, the treatment temperature is 80℃, and the stirring rate is 500r / min, so as to achieve comprehensive modification of solid fuel;

[0069] S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified coal.

[0070] Comparative Example 1

[0071] S1: dissolving the coal to be modified in deionized water to obtain a mixed slurry, the solid-liquid ratio of the mixed slurry is 1:20, stirring the mixed slurry to achieve comprehensive modification of the solid fuel, the treatment time is 30 minutes, the treatment temperature is 25°C, and the stirring rate is 800r / min;

[0072] S2 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified coal.

[0073] Comparative Example 2

[0074] S1: dissolving the coal to be modified in deionized water to obtain a mixed slurry, wherein the solid-liquid ratio of the mixed slurry is 1:20;

[0075] S2 passes H2SO4 into the mixed slurry. Since the pH of the mixed slurry is stabilized at 2.5 after continuous introduction of undesulfurized flue gas, it is necessary to ensure that the pH of the mixed slurry is stabilized at 2.5. After a period of reaction, the comprehensive modification of the solid fuel is achieved. The treatment time is 30 minutes, the treatment temperature is 25°C, and the stirring rate is 800r / min.

[0076] S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified coal.

[0077] Comparative Example 3

[0078] S1: dissolving the coal to be modified in deionized water to obtain a mixed slurry, wherein the solid-liquid ratio of the mixed slurry is 1:20;

[0079] S2 uses 3000ppm SO2+5%O2+15%CO2 mixed with balance gas N2 to simulate undesulfurized flue gas and directly introduces it into the mixed slurry. The treatment time is 30min, the treatment temperature is 25℃, and the stirring rate is 800r / min, so as to achieve comprehensive modification of solid fuel;

[0080] S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified coal.

[0081] The modified coal obtained in Example 1 and Comparative Examples 1 to 3 were respectively subjected to demineralization performance testing, crystal structure testing, pore structure testing, and surface chemical composition and element content testing. The results are as follows: Figures 2 to 6 As shown, the flue gas micro-nano bubbles in the figure are the modified coal obtained in Example 1, the deionized water is the modified coal obtained in Comparative Example 1, the H2SO4 is the modified coal obtained in Comparative Example 2, and the flue gas is the modified coal obtained in Comparative Example 3.

[0082] (1) Demineralization performance test

[0083] Table 1 shows the content and occurrence forms of inorganic elements in the coal to be modified used in Example 1 and Comparative Examples 1 to 3.

[0084] Table 1 Content and occurrence form of inorganic elements in the coal to be modified

[0085]

[0086] Figure 2 is the removal rate of minerals in the modified coal obtained in Example 1 and Comparative Examples 1 to 3, Figure 3 is the total content of acid infusible minerals in the modified coal obtained in Example 1 and Comparative Examples 1 to 3, wherein:

[0087] Removal rate = Na / Ca / / Mg / Fe content in modified coal / Na / Ca / / Mg / Fe content in raw coal. Comprehensive removal rate = (Na+Ca+Mg+Fe) content in modified coal / (Na+Ca+Mg+Fe) content in raw coal.

[0088] from Figure 2 It can be seen that compared with deionized water coal washing, acid washing and flue gas coal washing can effectively improve the mineral removal rate in coal. The removal rate of each element in flue gas coal washing is roughly equivalent to that in H2SO4 coal washing, while flue gas micro-nano bubble coal washing can further improve the mineral removal rate in coal. Figure 3 It can be seen that the additionally removed minerals are mainly acid-insoluble minerals (mainly silicates and aluminosilicates), which indicates that the flue gas micro-nano bubbles can react with acid-insoluble minerals, destroy the lattice structure, promote the transformation of acid-insoluble minerals, and thus improve the mineral removal rate.

[0089] (2) Crystal structure

[0090] The modified coal obtained in Example 1 and Comparative Examples 1 to 3 was subjected to XRD test and Raman test respectively to obtain the structural derivative behavior of the modified coal. The XRD results and Raman results were subjected to peak separation to obtain the following related parameters:

[0091] XRD: After peak separation of 002 peak, the aromaticity degree of coal is obtained, and the calculation formula is as follows:

[0092]

[0093] Wherein, d002 is the distance between the single layers of the aromatic layer of the coke microcrystal structure; Lc is the microcrystal stacking height perpendicular to the aromatic layer; La is the microcrystal size parallel to the aromatic layer; θ002 and θ100 are the diffraction angles corresponding to the 002 peak and the 100 peak respectively; β002 and β100 correspond to the half-height width of the 002 peak and the 100 peak; λ is the wavelength of the incident light, generally λ = 0.15406nm; k1 and k2 are the waveform factors, generally k1 = 0.89; k2 = 1.84.

[0094] The degree of aromaticity fa is used to characterize the degree of graphitization, and the integrated intensities (areas) of the 002 peak and the γ peak obtained by XRD peak fitting can represent the number of aromatic carbon atoms (Car) and the number of aliphatic carbon atoms (Cal), respectively.

[0095]

[0096] Figure 4 The microcrystalline structure parameters of the modified coal obtained in Example 1 and Comparative Examples 1 to 3 vary from Figure 4It can be seen that deionized water coal washing has no effect on the microcrystalline structure of coal, while H2SO4 and flue gas coal washing have almost the same effect on the microcrystalline structure of coal, mainly because the acid formed by flue gas dissolving in water also produces H ions, which is the same as the core essence of H2SO4. H ions will promote the breakage of branch chains or bridge chains in the coal structure, so they will promote the interlayer spacing of the microcrystalline structure (increase of d002) and the increase of stacking height (increase of Lc), and turn the macromolecular structure into a small molecular weight structure (decrease of La). With the breakage of bridge chains and branch chains, the remaining structures are stable structures, such as benzene rings, so the degree of aromaticity increases (increase of fa). After micro-nano bubble coal washing, the generated free radicals such as ·OH and ·O have higher electronic energy than ·H, and can also destroy benzene rings or heterocyclic organic structures, so they will further promote the increase of interlayer spacing and the formation of smaller molecular weight organic structures. The internal organic links between different aromatic layers will also be destroyed, resulting in a decrease in stacking height. The destruction of organic structures such as benzene rings leads to a significant decrease in the aromaticity of coal.

[0097] Raman: For the first order peak of Raman (800-2000cm -1 ) was processed into D1 peak, D2 peak, D3 peak, D4 peak and G peak, among which D1 peak was 1350cm -1 The peak, usually called the defect band, corresponds to the graphite lattice vibration mode with A1g symmetry and is attributed to in-plane defects such as defects and heteroatoms; the D2 peak is at 1620 cm -1 The peak is always present with the G1 peak, and its intensity decreases with the increase of carbon ordering degree. The D3 peak is usually a very wide band around 1500-1550cm-1, which is considered to be the manifestation of sp2 bonds in amorphous carbon, such as organic molecules, molecular fragments or functional groups in substances with low carbon ordering degree. The D3 peak may be related to the reaction site, thus affecting the reactivity of coke. The D4 peak is 1150cm-1, which only appears in substances with low carbon ordering degree, such as bituminous coal and coal coke. The D4 peak may be attributed to the sp3-sp2 mixing site at the edge of the crystallite or the stretching vibration of C-C and C=C of polyenes, and it may also be due to the reaction site. The G peak is 1580cm-1. -1 The peak corresponds to the stretching vibration peak of E2g symmetry in the aromatic layer of graphite crystal. The characteristics of Raman spectrum have been shown to have a good correlation with the degree of ordering of carbon structure. Therefore, Raman spectrum can be used to analyze the effect of heat treatment on the evolution of coke structure. The following three band area ratios are mainly calculated: I D1 / I G ,I D3 / I G and I G / I ALL , where I D1 / I G is the relative content of unstable structure, I D3 / I G is the loudness content of the amorphous structure, I G / I ALL is the relative content of graphite structure.

[0098] like Figure 5 As shown in the figure, after deionized water coal washing, ID1 / IG, ID3 / IG and IG / IALL are almost the same as those of the original coal, indicating that deionized water coal washing will not change the structure and content of residual carbon, amorphous carbon and graphite carbon in coal, while after H2SO4 and flue gas coal washing, ID1 / IG and ID3 / IG drop rapidly, and IG / IALL rises sharply, indicating that the H ions in the solution during H2SO4 and flue gas coal washing will promote the elimination of residual carbon and amorphous carbon, reduce the content of residual carbon and amorphous carbon in coal, thereby increasing the relative content of graphite carbon, which is manifested as an increase in the degree of graphitization. After coal washing with flue gas micro-nano bubbles, ID1 / IG and ID3 / IG showed an increasing trend, while IG / IALL dropped sharply. This was mainly because the high reaction activity of free radicals such as ·OH and ·O generated by flue gas micro-nano bubbles can destroy the graphite carbon structure (such as benzene ring or heterocyclic organic structure) and transform it into amorphous carbon and residual carbon. The comprehensive performance is that the relative content of residual carbon and amorphous carbon is higher than that of H2SO4 and flue gas washing. This fully shows that coal washing with flue gas micro-nano bubbles will promote the decomposition of graphite carbon structure and reduce the degree of aromatization of coal.

[0099] (3) Pore structure

[0100] The modified coal obtained in Example 1 and Comparative Examples 1 to 3 was analyzed by using an adsorption tester, the total specific surface area was tested by using the BET model, and the pore size distribution of the coke was determined by using the BJH model.

[0101] Table 2 Pore structure parameters of modified coal in Example 1 and Comparative Examples 1 to 3

[0102]

[0103] Table 2 shows the measured pore structure parameters of modified coal. Deionized water washing has little effect on the specific surface area and pore volume of coal. H2SO4 and flue gas washing will increase the micropore area, external surface area, total specific surface area and pore volume of coal to a certain extent due to the bond breaking effect of ·H radicals. After coal washing with flue gas micro-nano bubbles, due to the destructive effect of strong oxidizing free radicals such as ·OH and ·O, the molecular weight of the coal base is reduced, the degree of aromatization is reduced, the pores inside the coal are effectively opened, and a pore-rich structure is formed, which further increases the micropore area, external surface area, total specific surface area and pore volume of the coal.

[0104] (4) Surface chemical composition and element content

[0105] XPS test was performed on the modified coal obtained in Example 1 and Comparative Examples 1 to 3 to obtain the surface chemical composition and element content of the modified coal. The S2p and N1s spectra of the XPS results were subjected to peak separation, and the electron binding energies corresponding to different structures were as follows:

[0106] S2p:

[0107] Pyrite (158~159.6eV)

[0108] Sulfide (161.2~163.6eV)

[0109] Thiophene (164-164.4 eV),

[0110] Sulfoxide (165~166eV)

[0111] Sulfone (167~168.3eV)

[0112] Sulfate (168.4~175eV)

[0113] N1s:

[0114] Pyridinic N (N-6): The binding energy is 398.7 eV ± 0.3 eV. This nitrogen atom is usually connected to a carbon atom and a hydrogen atom to form a five-membered ring structure.

[0115] Amino, imine, and amide nitrogen (NH): The binding energy is located at 399.8 eV ± 0.2 eV. These nitrogen atoms can form bonds with hydrogen, carbon, and / or other elements.

[0116] Pyrrolic and pyridonic N (N-5): The binding energy is at 400.3 eV ± 0.2 eV. These nitrogen atoms usually participate in the formation of five-membered or six-membered heterocyclic structures.

[0117] Quaternary Nitrogen (NQ): The binding energy is at 401.4 eV ± 0.3 eV. This nitrogen atom acts as a substituent in the aromatic graphene structure and is connected to four carbon atoms.

[0118] Pyridine-N-oxide or Ammonia (NO): The binding energy is at 402.8 eV. This nitrogen atom can be part of a pyridine ring, in which the nitrogen atom is oxidized, or it can be the nitrogen in an ammonia molecule.

[0119] Adsorbed Nitrogen Oxides (N-OX): The binding energy is located at 405.0 eV ± 0.5 eV. These nitrogen atoms usually form bonds with oxygen atoms and may be connected to other elements such as carbon or hydrogen.

[0120] Figure 6 The S / N distribution characteristics of the modified coal obtained in Example 1 and Comparative Examples 1 to 3 are as follows. Figure 6 It can be seen that water washing will not change the distribution of S forms in coal. H2SO4 and flue gas coal washing will remove some inorganic sulfur such as pyrite, water-soluble sulfides and sulfates in coal, but will not destroy the organic sulfur structure in the form of thiophene, sulfoxide and sulfone. Flue gas micro-nano bubble coal washing will promote the decomposition of some thiophenes in coal and convert them into sulfoxides and sulfones. It will also promote the decomposition of some sulfoxides and sulfones and convert them into sulfides and sulfates, ultimately reducing the overall content of organic sulfur in coal.

[0121] For N, from Figure 6 It can be seen that water washing will not change the distribution of N forms in coal, H2SO4 and flue gas coal washing will remove some NH (amino, imine, amide nitrogen), NQ (quaternary ammonium nitrogen), NO (oxidized pyridinic nitrogen or ammonia nitrogen), and N-OX (adsorbed nitrogen oxides) in coal, and will not destroy the organic nitrogen structure in the form of pyridinic nitrogen and pyrrolic nitrogen. Flue gas micro-nano bubble coal washing will promote the decomposition of some pyridinic nitrogen and pyrrolic nitrogen in coal and convert them into NH (amino, imine, amide nitrogen), NQ (quaternary ammonium nitrogen), NO (oxidized pyridinic nitrogen or ammonia nitrogen), and N-OX (adsorbed nitrogen oxides).

[0122] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A comprehensive modification method of solid fuel based on flue gas micro-nano bubbles, characterized in that: The solid fuel comprehensive modification method is specifically: S1 dissolving the solid fuel to be modified in a liquid solvent to obtain a mixed slurry; S2 introduces the undesulfurized flue gas into the mixed slurry in the form of micro-nano bubbles, so that under the joint action of the multi-free radicals generated by the micro-nano bubbles and the complex flue gas components, the solid fuel is demineralized and the physical and chemical properties of the solid fuel are improved, thereby achieving comprehensive modification of the solid fuel; S3 performs solid-liquid separation and drying on the modified mixed slurry to obtain modified solid fuel.

2. The solid fuel comprehensive modification method according to claim 1, characterized in that: In step S1, the liquid solvent is pure water, boiler drum water, domestic water or water after deep treatment in a desulfurization wastewater treatment system.

3. The comprehensive modification method of solid fuel according to claim 1, characterized in that: In step S1, the particle size of the solid fuel to be modified is less than 200 μm.

4. The comprehensive modification method of solid fuel according to claim 1, characterized in that: In step S1, the solid-liquid ratio of the mixed slurry is 1:20 to 1:

50.

5. The comprehensive modification method of solid fuel according to claim 1, characterized in that: In step S2, the size of the micro-nano bubbles is 100 nm to 10 μm.

6. The comprehensive modification method of solid fuel according to claim 1, characterized in that: In step S2, the treatment time is 30 minutes to 2 hours, and the treatment temperature is 20°C to 80°C.

7. The comprehensive modification method for solid fuel according to any one of claims 1 to 6, characterized in that: In step S2, the slurry is stirred while the flue gas is introduced, and the stirring rate is 200 r / min to 1500 r / min.

8. Modified solid fuel obtained by the comprehensive modification method of solid fuel as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for releasing organics from shale and like materials to produce a liquid shale fuel

    CN101506331A

  • Process for producing high calorific value water-coal slurry by utilizing coal or coal gangue and coal gasification process adopting process

    CN107267236A

  • Method for extracting arsenic in coal by flue gas under ultraviolet light irradiation

    CN109266418A

  • Multielement mixed liquid-like fuel and preparation method thereof

    CN110437894A

  • Flue gas enhanced washing pretreatment method for ash reduction and quality improvement of fire coal

    CN111925851A